Lay Knowledge and Beliefs Toward Dementia Among the Black African Populations in the UK and Africa: Evidence Synthesis of Qualitative Studies - Raphael Chinedu Mokwenye (SAGE Publishing, 2024)
Background: The high prevalence of dementia among Black Africans, coupled with their lower engagement with dementia specialist services in the UK, underscores the urgency of understanding lay knowledge and beliefs about dementia in the group. Studies reporting lay knowledge of dementia in the UK tended to conclude that Black Africans lack dementia knowledge, presumably based on biomedical assumptions, without taking into consideration the Black Africans' lay dementia knowledge and beliefs about dementia. The current study, therefore, investigated the Black African populations' lay knowledge and beliefs toward dementia in Africa, comparing how this relates to the findings in the UK literature. Methodology: The researcher thoroughly searched electronic databases from September 2017 to October 2022 for qualitative research exploring how Black African populations perceived and experienced dementia, which informed the Black Africans' dementia knowledge in Africa and the UK. The review included qualitative studies with African populations published in peer-reviewed journals with available abstracts and full text in English. Studies outside the UK and Africa, as well as quantitative research and studies with health practitioners, were excluded. A grounded theory approach informed the thematic analysis. The researcher reported the Black Africans' lay knowledge and beliefs toward dementia, informed by participants' experiences and meanings of dementia. Results: Twenty-two studies (n = 22) met the eligibility criteria and were appraised and included in the review. All the UK papers were a multi-modeling of ethnicity in the study. Nine studies (n = 9) were conducted in the UK. Thirteen studies (n = 13) are conducted in Africa, (5 [n = 5] studies from South Africa, 2 [n = 2] from Tanzania, 1 [n = 1] from Congo, 2 [n = 2] from Uganda, 2 [n = 2] from Nigeria, and 1 [n = 1] from Ghana). All the studies were valuable. The researcher identified and developed 4 themes as they emerged from the studies: (i) Dementia witchcraft paradigm, (ii) Dementia older age paradigm, (iii) Dementia disease and illness paradigm, and (iv) Dementia identity paradigm. Discussion/Conclusion: The lay knowledge and beliefs about dementia among Black African populations were foregrounded in sociocultural distinctiveness, and some understanding intersected with biomedical knowledge about dementia. Further empirical study in the UK is essential. Implications for policy and practice: A better understanding of lay knowledge and beliefs about dementia among Black African populations can improve dementia care, providing culturally sensitive and tailored support for Black African communities.